Oil painting essentials : mastering portraits, figures, still life, landscapes, and interiors - Kreutz, Gregg, 1947-; Watson-Guptill Publications (Berkeley : Watson-Guptill Publications, 2016)
"From the author of the classic Watson-Guptill best seller Problem Solving for Oil Painters comes an essential guide demonstrating the universal oil painting techniques that allow artists expand their horizons, break out of ruts, and master a variety of subjects, including figures, portraits, still life, landscapes, and interiors"--
Includes index.
Keywords: Painting -- Technique